THE SRY GENE VARIATIONS AMONGST SELECTED MADURA CATTLE POPULATIONS - Koko Wisnu Prihatin; Sucik Maylinda; Luqman Hakim (Universitas Syiah Kuala, 2018)
The aim of this study was to determine the diversity of the sex-determining region Y (SRY) gene in Madura cattle bulls that had specifically selected for the production of frozen semen. DNA was isolated from the whole blood derived from 5 Madura cattle bulls and the SRY gene amplification carried out using polymerase chain reaction (PCR) with SRY-4 as a primer followed by DNA sequencing. Results revealed the proximity of the Madura cattle SRY genes to the Bos indicus SRY genes, furthermore this study also proved the existence of variation in Madura cattle SRY gene caused by mutation and deletion of nucleotides. It was concluded that the variations in Madura cattle SRY genes still persist even in the specifically selected populations with similar phenotype.